Social policy and the judicial making of Europe: capital, social mobilisation and minority social influence - Konstantinos Alexandris Polomarkakis (European Law Open, 2022)
This article puts forward a cohesive narrative to explain the contribution of European social policy to the judicial making of Europe. By making a case for the inclusion of social policy as part of the discourse on the constitutional practice of the Court of Justice of the European Union, together with focusing on a socio-legal deconstruction of four seminal social policy judgments of the Court (Defrenne II, Von Colson, Harz and Francovich), the article undertakes a systematic approach to tracing the contribution of the field, and more specifically of its labour and non-discrimination law strands. To formulate its socio-legal analysis, the article adopts an explanatory framework, which draws on Bourdieu’s concepts of capital and field, the theory of legal mobilisation and Moscovici’s minority social influence, and which is applied to the selected judgments as a case-study. The framework enables the analysis to shed light on the dynamics between stakeholders in the social dimension of the European legal field and to persuasively showcase how social policy case-law, despite its sui generis dynamics, merits to have a place in the conversations surrounding the transformation of Europe.